2017
DOI: 10.1515/eces-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Heavy Metals and Radionuclides Accumulated in the Soil and Biota Samples Collected in Svalbard, Near Longyearbyen

Abstract: Heavy metals and radioactive compounds are potentially hazardous substances for plants, animals and humans in the Arctic. A good knowledge of the spatial variation of these substances in soil and primary producers, and their sources, is therefore essential. In the samples of lichen Thamnolia vermicularis, Salix polaris and Cassiope tetragona, and the soil samples collected in 2014 in Svalbard near Longyearbyen, the concentrations of the following heavy metals were determined: Mn, Ni, Cu, Zn, Cd, Pb and Hg, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Near Longyearbyen there were noticeably higher concentrations of Ni (0.014 mg/g) compared to the rest of Svalbard (0.004 mg/g) [40]. Other macro-, and microelements are at a similar level in the areas surrounding Longyearbyen and the natural areas of the Advent valley: 0.307 mg/g Mn, 0.050 mg/g Cu and 0.151 mg/g Zn.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Near Longyearbyen there were noticeably higher concentrations of Ni (0.014 mg/g) compared to the rest of Svalbard (0.004 mg/g) [40]. Other macro-, and microelements are at a similar level in the areas surrounding Longyearbyen and the natural areas of the Advent valley: 0.307 mg/g Mn, 0.050 mg/g Cu and 0.151 mg/g Zn.…”
Section: Discussionmentioning
confidence: 87%
“…The concentrations of heavy metal were of the same magnitude (>10 µg/g) in both places [10,31,40]. Baret et al [68] showed the existence of a strong correlation between the blue shift and the severity of damage to vascular plants, mosses and lichens.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This area is considered heavily affected by specific atmospheric circulation patterns bringing various xenobiotics from Europe's industrialized areas, especially in winter (Birks et al 2004). According to Kłos et al (2017) also sea aerosol is a source of anthropogenic Cs-137, Pb-210, Th-231, Pb, and Hg which affect the soil and biota near Longyearbyen. The same authors proved elevated levels of Ni in moss, lichen, and vascular plant samples (Salix polaris Wahlenb.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium may occur due to leaching of living or dead tissue of other plants [20]. The main sources of the elements such as Ni, Fe, Sb, and Cd can be associated to the transport and industrial activity [21,22]. The Botanical garden is situated in the vicinity of the city and it is surrounded by the national roads.…”
Section: Resultsmentioning
confidence: 99%